2013
DOI: 10.1016/s1872-2067(12)60535-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation and cleavage of the C-O bonds in the lignin model compound phenethyl phenyl ether over a nickel-based catalyst

Abstract: Phenethyl phenyl ether (PPE) was selected as a typical lignin model compound and hydrogenated and cleaved over two readily accessible nickel-based catalysts, which could be easily separated from the product mixture. The results revealed that the reduction of the nickel catalyst with gaseous hydrogen produced a species capable of achieving higher activity towards C-O-C bond cleavage compared to the Ru/C and Pd/C catalysts. The selectivity of the C-O-C bond cleavage over the Ni/C catalyst was 85%, and higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Product 4 reached a maximum yield of 25% and both guaiacol (product 5) and p-anisic acid (product 6) were produced, which was also confirmed by previous literature under aerobic conditions [42]. With Au/meso-Fe2O3 as a catalyst, the hydroxyl group of the Cα position was oxidized, which significantly lowered the C-O bond energy in the ketone form compared to the initial benzylic alcohol form [43]. Finally, products 5 and 6 reacted to form product 7 under esterification with a low yield.…”
Section: Entrysupporting
confidence: 87%
“…Product 4 reached a maximum yield of 25% and both guaiacol (product 5) and p-anisic acid (product 6) were produced, which was also confirmed by previous literature under aerobic conditions [42]. With Au/meso-Fe2O3 as a catalyst, the hydroxyl group of the Cα position was oxidized, which significantly lowered the C-O bond energy in the ketone form compared to the initial benzylic alcohol form [43]. Finally, products 5 and 6 reacted to form product 7 under esterification with a low yield.…”
Section: Entrysupporting
confidence: 87%
“…The reduced Ni-based catalysts also demonstrated to be more active than a Ru-based catalyst for cleavage in ether bond using lignin model compound and hydrogen atmosphere (Song et al, 2013).…”
Section: Effects Of Catalysts and Temperature On Products Yieldsmentioning
confidence: 99%
“…Xin et al (2014) found that partial depolymerization of enzymolysis lignin via mild hydrogenolysis over raney nickel enhanced the solubility of the depolymerized lignin and reduced the molecular weight with increased hydroxyl numbers. Song et al (2013) reported that the reduced nickel-based catalysts played an important role in the hydrogenolysis of the C-O-C bonds in two lignin model compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Methyltrioxorhenium (MTO) in combination with H2O2 catalyzed lignin Ni-based catalysts were used for lignin hydrogenation/hydrogenolysis in 1940 [299]. Ni catalysts supported on carbon and magnesium oxide were found to be active for C-O bond cleavage of model compounds as well as selectively hydrogenolyzing the aryl ether C-O bonds of β-O-4 without disturbing the arenes [278,300,301]. The alcohol solvents were used as a hydrogen donor for the hydrogenolysis of lignin [278].…”
Section: Lignin As Feedstockmentioning
confidence: 99%